On having royal relatives: Interpreting misidentifications in a case of impaired person recognition. - Francis, DR; Riddoch, M; Humphreys, G (2004)
We report data from a patient, NE, who after surviving encephalitis made misidentification responses to faces known to her premorbidly. NE frequently mistook one famous person for another, one relative for another, and, under some conditions, believed that a picture of a famous person actually depicted one of her relatives. Unlike previously reported patients who have misidentified faces, NE (1) performed reasonably well on tests of facial perception, (2) showed no obvious executive deficits in tests of frontal lobe function, and (3) showed an ability to constrain her misidentification responses in certain situations. A cognitive neuropsychological investigation revealed that NE was able to judge misidentified faces as familiar but failed to access precise semantic information. There were also semantic deficits when knowledge of people was probed through nonvisual modalities-for example, when naming people from definition. We argue that a semantic, as opposed to executive, deficit plays the major (though probably not sole) role in NE's misidentification responses, and we consider how the inter-active activation model of face recognition (Burton, Bruce, and Johnston, 1990) can account for such disorders of person recognition more comprehensively than the Bruce and Young (1986) model.